A retrospective analysis of the position of catheter tip and the incidence of thrombosis in breast cancer patients with implantable venous access port placement (乳腺癌患者静脉输液港导管尖端位置与血栓发生的回顾性分析) - WU Lingxiao (伍凌萧); WANG Qing (王庆) (中西医结合护理)
Objective The relationship between catheter tip location and catheter-associated venous thrombosis was analyzed by retrospectively summarizing the clinical data of 60 breast cancer patients with implantable venous access port placement. Methods The clinical data of 60 breast cancer patients treated in the Department of Breast and Thyroid Surgery from May 2020 to December 2021 after chest wall placement of implantable venous access port were collected, and the relationship between the position of catheter tip and the occurrence of catheter-related venous thrombosis was analyzed. Results Among 60 breast cancer patients, 15 and 45 patients were treated via left internal jugular vein or right internal jugular vein, respectively. A total of 20 patients (33. 33%) developed catheter-related venous thrombosis, including 6 cases (40. 00%) in left internal jugular vein and 14 cases (31. 11%) in right internal jugular vein (χ2 =0. 40, P=0. 542. The catheter tip was located in superior vena cava, which was lower than the junction level between superior vena cava and right atrium (group A) in 25 cases (T4 or T5 vertebral body level), and there were 14 cases (56. 00%) with catheter related venous thrombosis. There were 35 cases (T7 or T8 vertebral body level) with the catheter tip at the junction between superior vena cava and right atrium (group B), and 6 cases (17. 14%) had thrombus catheter related vein, there was a significant difference between group A and group B (χ2=9. 90, P=0. 002)Conclusion Catheter-related vein thrombosis is one of the more common postoperative complications of implantable venous access port placement. There was no significant difference in the incidence of catheter-related vein thrombosis between access via left side of the internal jugular vein and the right internal jugular vein. However, the catheter tip location could influence the incidence of catheter-related vein thrombosis, and lower incidence of catheter-related vein thrombosis was associated the catheter tip location at junction level between superior vena cava and right atrium. (目的 通过对 60 例乳腺癌患者输液港导管尖端位置的临床资料回顾性总结, 分析导管尖端位置与导管相关性静脉血栓形成的关系。方法 收集 2020 年 5月—2021 年 12 月就诊于湘西自治州人民医院乳腺、甲状腺外科60例乳腺癌患者安装胸壁静脉输液港后的临床资料, 分析输液港导管尖端位置与导管相关性静脉血栓发生情况的关系。结果 60例乳腺癌患者采用左侧颈内静脉或右侧颈内静脉置港化疗的人数分别为 15例 和45 例。共有 20 (33. 33%)例患者发生导管相关静脉血栓, 其中左侧颈内静脉6(40. 00%)例, 右侧颈内静脉 14(31. 11%)例, 差异无统计学意义(χ2=0. 40, P=0. 542)。导管尖端位于上腔静脉内, 低于上腔静脉与右心房交界水平以上(T4或T5椎体水平)者25例(A组), 其中有导管相关静脉血栓者14(56. 00%)例; 导管尖端位于上腔静脉与右心房交界水平(T7或T8椎体水平)者35例(B组), 其中有血栓导管相关静脉血栓者6(17. 14%)例, 差异有统计学意义(χ2 =9. 90; P=0. 002)。结论 导管相关静脉血栓是静脉输液港术后较常见的并发症, 经左侧颈内静脉和右侧颈内静脉安装输液管, 其导管相关静脉血栓发生率无明显差异, 但输液港导管尖端位置对导管相关静脉血栓发生率产生较明显的影响, 其导管尖端位置位于上腔静脉与右心房交界水平者血栓发生概率较小。)